Innovative Leadership Management: The Pattern of School Quality Development at SMP Muhammadiyah 2 Inovasi Malang - M. Ubaidillah Ridwanulloh; Syamsul Huda; Rofiqul Umam (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2022)
This study aimed to examine innovative school leadership management in order to improve school quality. Innovation strategies in the aspects of school leadership include the promotion of the work ethic of human resources, implementation of the curriculum, learning methods and media, and school facilities and infrastructure. This research was conducted by direct field observation at SMP Muhammadiyah 2 Inovasi, Malang, thus involving in depth interview and repeated observations. This research applied qualitative approach with descriptive analysis to describe the object of study comprehensively. The results showed that school management based on innovation as a strategy to improve school quality had proven successful. In the end, the school experienced an increase in the number of enrolled students, academic and non-academic achievements. Moreover, the number of graduates who continued to a higher level was doubled.